1992
DOI: 10.1111/j.1469-8137.1992.tb05656.x
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the discrete root epidermis of Pistia stratiotes L. after perturbation of the meristem

Abstract: SUMMARYPerturbation of meristems of adventitious roots of Pistia resulted in abnormal pattems of cell division in the quiescent centre including the pole of the normally discrete epidermis. Two of the methods used, radiation from incorporated tritiated thymidine and cold treatment, also produced abnorma) patterns in the lateral primordia present within the apices of the adventitious roots. Cells of the monostromatic epidermal shell divided periclinically in some roots and some primordia where all previous divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…α-tocopherol [ 54 ] controls the prominent metabolic bioconversions during ripening viz. cell division [ 55 , 56 , 57 , 58 ], cell wall expansion [ 59 ] and organogenesis [ 60 ]. The fundamental role of antioxidative system consisting CAT, SOD and ascorbate glutathione during the ripening of tomato reduced the oxidative damage at breaker stage.…”
Section: Effect Of Polyamines On Postharvest Physiology Antioxidamentioning
confidence: 99%
“…α-tocopherol [ 54 ] controls the prominent metabolic bioconversions during ripening viz. cell division [ 55 , 56 , 57 , 58 ], cell wall expansion [ 59 ] and organogenesis [ 60 ]. The fundamental role of antioxidative system consisting CAT, SOD and ascorbate glutathione during the ripening of tomato reduced the oxidative damage at breaker stage.…”
Section: Effect Of Polyamines On Postharvest Physiology Antioxidamentioning
confidence: 99%
“…Unlike the primary root and shoot apices, which originate at the ends of the embryonic plant axis, lateral roots have an endogenous origin and are initiated postembryonically. In general, lateral roots originate from a small number of the founder cells of the internal tissue of the parental root, usually in the pericycle, although in ferns they are derived from endodermis while in some species of water plants they are derived from both pericycle and endodermis (Cutter, 1971;Lin and Raghavan, 1991;Clowes, 1992). In each case, however, their development involves a continuous change of form.…”
Section: Origin and Morphological Changes Of The Developing Lateral Rootmentioning
confidence: 99%
“…It is involved in removing AOS and regenerating a-tocopherol (an important lipid-phase antioxidant, Asada 1994), is utilized in cell metabolism and may be involved in the control of growth (Navas and Gomez-Diaz 1995), cell division (Liso et al 1984(Liso et al , 1988Clowes 1991;Kerk and Feldman 1995), cell wall expansion (Takahama and Oniki 1994) and organogenesis (Joy et al 1988) (for reviews, see Smirno 1996;Noctor and Foyer 1998). It has been suggested that ripening of climacteric fruit is initiated by ethylene, although it is not the sole determinant of fruit ripening (Picton et al 1993).…”
Section: Introductionmentioning
confidence: 97%